(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The college library has been undergoing a great change in its role, though slowly, and is now on the threshold of being transformed into an academic unit of the college. To accelerate this transformation, there is need to educate the masters. The introduction of the academic library system, under which the library will become a “department of library services”, will enable the college library to undertake the task of reorganizing and managing the library by providing better facilities and services. The objectives should be that a college library should become an instrument of instruction. In order to determine, how far it has succeeded in achieving the objective, one should determine the extent to which the users (students and faculty) use the resources of the library as an integral part of the curriculum. In other words it means that teaching in the classroom must depend more on library than the text books. The library must become an integral part of teaching programme.